Comparison of circulating DNA in malignant neoplasia from diverse locations: Investigating a diagnostic role - Swati Kumari; Sridhar Mishra; Nuzhat Husain; Tripti Verma; Vandana Tiwari; Mohamed Kaif; Akash Agarwal; Madhup Rastogi; Saumya Shukla; Abhinav Arun Sonkar (Wolters Kluwer Medknow Publications, 2022)
Context: Circulating free DNA (cfDNA) analysis has emerged as novel noninvasive diagnostic biomarker in several solid tumors. Raised levels have been reported in several malignancies and may correlate with clinicopathological and treatment response. The current study was designed to assess the diagnostics of cfDNA in different tumor types of malignancies correlating with tumor (T), nodes (N), and metastases (M) stage. Design: Serum samples were collected from treatment naïve cases with histologically diagnosed tumors including 23 brain tumors, 48 breasts, 50 gallbladder carcinoma (GBC), 13 lungs, 68 oral squamous cell carcinoma (OSCC), and 25 normal controls. CfDNA was quantified with real-time polymerase chain reaction (PCR), Invasive ductal carcinoma (IDC) using beta-globin gene amplification. Cut off values for diagnostics were calculated using receiver operating curve analysis. Results: Contrary to other cfDNA studies where it was postulated that cfDNA would not cross the blood-brain barrier and reach the systemic circulation, we found detectable cfDNA in glioma with median (Q1-Q3) of 349.22 ng/ml (19.87-1276.58). Median cfDNA concentration in breast, gallbladder, lung, oral and normal controls was 328.72 (128.38-624.44), 778.50 (589.88-1864.35), 348.73 (194.67-483.61), 386.27 (47.88-959.67), and 74.12 (49.66-120.00), respectively. Grades I and II glioma had significantly lower levels compared to Grades III and IV (P = 0.0001). Significant difference in median cfDNA values in IDC and GBC was observed with increasing tumor grades, stage, T stage, nodal stage and metastasis and with stage of OSCC cases. Conclusion: CfDNA levels showed good diagnostic discrimination in glioma, GBC, breast, lung carcinoma, and OSCC. Significant increase in titers was evident with increase in cancer stage from I to IV in breast, GBC and OSCC.